Comparison of low pressure versus standard pressure pneumoperitoneum for elective laparoscopic cholecystectomy in a tertiary care institute of western India - Gohil, Ajit (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy has proven beyond doubt to be the gold standard in the management of symptomatic cholelithiasis and other gall stone diseases. The aim of this study was to compare the use of the low-pressure pneumoperitoneum (defined as 7-9 mm Hg) with the use of standard pressure pneumoperitoneum (defined as 14 mm Hg) in patients undergoing laparoscopic cholecystectomy in a prospective randomized manner. Methods: This randomized prospective study was carried out in the Department of General Surgery in a tertiary care PDU hospital, in Rajkot, India, from July 2014 to October 2016, with a sample size of 50 patients. Patients were randomized into two groups, one group with 25 patients was undergone laproscopic cholcystectomy with standard pressure pneumoperitoneun at 14 mm hg (SPLC) while the other group with 25 patients was undergone laproscopic cholecystectomy with low pressure pneumoperitoneum at 7-9 mm hg (LPLC). Results: Incidence and intensity of post-operative pain were significantly lower in LPLC group compared to SPLC group. The average change in systolic BP and diastolic BP in patients who underwent LPLC and SPLC was not statistically significant. Average hospital stay for LPLC group are 1.92 days and for SPLC group its 2.48 days. Conclusions: Though surgeon experience quite more difficulty in dissection during low pressure pneumoperitoneum and operative time is quite high, it is significantly advantageous in terms of post-operative pain, use of analgesics, less shoulder tip pain and hospital stay. It is feasible and safe. There was no significant change in SBP and DBP in both groups.